Measurements of the Higgs Boson in the H - τ τ decay channel - Howard, JR (2015)
The generation of vector boson mass via the Higgs mechanism in the Standard Model has been confirmed by the 2012 discovery of a candidate Higgs boson in the H→WW, H→ZZ, and H→γγ decay channels. In contrast, the Yukawa couplings hypothesized to provide the mass of fermions in the Standard Model have yet to be observed. The H→ττ decay channel currently provides the best opportunity for observing these couplings. This thesis describes two separate but related searches for Higgs boson decays in the H→ττ decay channel using proton-proton collisions recorded by the ATLAS detector. The first analysis is a general search for all Higgs boson production mechanisms leading to a H→ττ decay using 4.5 fb−1 of 7 TeV and 20.3 fb−1 of 8 TeV proton-proton collision data. A deviation from the background-only hypothesis is observed with a significance of 4.5σ for a hypothetical Higgs boson mass of mH = 125 GeV — a strong indication of a H→ττ signal. For the same mass point, the best fit value for the signal strength is found to be 1.43 +0.43−0.37 × the Standard Model expectation. The second analysis is a search for Higgs boson production in association with a vector boson using 20.3 fb−1 of 8 TeV proton-proton collision data. Results in the ZllH→τlτh channel indicate limits of 9.14 × the Standard Model expectation for VH signal production at mH = 125 GeV. In addition, two studies on enhancement of computing performance in the ATLAS trigger and data analysis pipeline are presented.